Sociological Dimensions of Representation: Othering & Stereotyping - Dhobi, Saleem (Patan Pragya, 2022)
This paper investigates into multiple forms and dimensions of representation employed in literary works and public affairs. It is a thorough study of secondary works published on the issues ranging from representation to stereotyping—general to specific sociological practices in writing. The article aims to examine the societal predicaments as depicted in writings and verbal expressions. More than this, the paper uncloaks the dominating temperament of majority community in culturally diverse societal setting. How the minority groups are treated by the socially and culturally privileged community is the corpus of the investigation. The article discusses the concept of representation by Stuart Hall and the concept of othering by Lajos Bronsin order for examining the other forms of representation. The meaning is constructed by the dominant community for underprivileged groups such as people of color in the United States of America, South Asians in the international space, and women in the global phenomena. The generalized views about any sociological category become the stereotypes which stigmatize the community in entirety. The individual drawbacks must not be associated with the distinctive features of a large sociological group as the process becomes unfair and biased.